Tunable coupling of two mechanical resonators by a graphene membrane. (26th May 2021) - Verbiest, G J; Goldsche, M; Sonntag, J; Khodkov, T; von den Driesch, N; Buca, D; Stampfer, C
Abstract: Coupled nanomechanical resonators are interesting for both fundamental studies and practical applications as they offer rich and tunable oscillation dynamics. At present, the mechanical coupling in such systems is often mediated by a fixed geometry, such as a joint clamping point of the resonators or a displacement-dependent force. Here we show a graphene-integrated electromechanical system consisting of two physically separated mechanical resonators—a hybrid graphene comb-drive actuator system and a suspended silicon beam—that are tunably coupled by the integrated graphene membrane. The graphene membrane, moreover, provides a sensitive electrical read-out for the two resonating systems showing 16 different modes in the frequency range from 0.4 to 24 MHz. In addition, by pulling on the graphene membrane with an electrostatic potential applied to silicon beam resonator, we control the mechanical coupling, quantified by the g -factor, from 20 kHz to 100 kHz. Our results pave the way for coupled nanoelectromechanical systems requiring controllable mechanically coupled resonators.